A CROSS-SECTIONAL STUDY ON SODIUM VALPROATE, CARBAMAZEPINE, AND LEVETIRACETAM INDUCING ENURESIS IN EPILEPTIC CHILDREN - SATHYAN, ARYA; SCARIA, RESHMA; S SHALINI, (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Enuresis or bedwetting is considered to be an underreported ADR of antiepileptic drugs (AEDs). This study assesses the incidence and comparative rate of occurrence of enuresis in children with epilepsy who are on AEDs treatment such as sodium valproate (SV); carbamazepine and levetiracetam (LEV). Methods: The study was conducted with a sample size of 32 patients. Both inpatients and outpatients between the age group >5–18 years of age previously diagnosed with epilepsy that is on monotherapy and polytherapy with SV or carbamazepine or LEV were included in the study. Patients with urinary complications or urogenital abnormalities past 3 months before admission were excluded from the study. Assessment of enuresis was done based on a questionnaire prepared from NICE guidelines and analyzed using SPSS software version 20. Results: Of 44 patients who were included in the study, only 34 came for review. Analysis of the questionnaire showed the occurrence of enuresis in 12 patients. Drugs prescribed versus assessment questions showed potent significance with eight questions; hence the hypothesis that the prescribed drugs can cause enuresis can be taken into consideration. The rate of occurrence of enuresis was analyzed in all the drugs with their respective doses, but the significant values were found only for SV 200 mg. Conclusion: This study shows the possibility of enuresis in LEV and SV treatment with a significant difference in SV. Furthermore, it showed a relation between the duration of treatment and the occurrence of enuresis.